Correlation of Perception Of Dental Esthetics Between A Prosthodontist And Patient: A Questionnaire Study (Journal of Pharmaceutical Negative Results, 2023)
Aim: To evaluate & compare esthetic perception by Prosthodontist as well as patient using QDA (Questionnaire on own Dental Appearance) and PEI (Prosthetic Esthetic Index). Materials and Methodology: The study was conducted on 44 participants, who were evaluated by a single Prosthodontist by using PEI Index, and another questionnaire filled by patients, evaluating their own esthetic appearance by using QDA index. Data was recorded and Spearman correlation coefficient analysis was done. Results: On the basis of Spearman correlation coefficient test, it showed that the R value was 0.374. This value shows weak but positive correlation between PEI & QDA. Conclusion: On basis of the results of the study, it can be concluded that the perception of Prosthodontist and perception of patient both are different but there was weak positive correlation between PEI & QDA.